Prestations- och kvalitetsstudie av maskiner för rensning av skogsdiken - Bertland, Per; Käll, Dan (2011)
Ditch cleaning is increasingly important in Swedish forestry. This study compare different concepts concerning machinery, namely two general-purpose excavators of different sizes, 8 tonnes and 15 tonnes, versus a dedicated machine constructed solely to deal with ditch-cleaning. The machines were tested on rough as well as on gentle terrain and on open terrain as well as in young stands in connection with thinning. The conclusions were that the excavators are more versatile and have greater capacity than the dedicated machine, while the latter excels in quality of work. Interestingly, there was no significant difference in performance between the both excavators.